Evaluation of primer pairs for eDNA‐based assessment of Ephemeroptera, Plecoptera, and Trichoptera across a biogeographically diverse region. Issue 6 (8th August 2022) - Brantschen, Jeanine; Pellissier, Loïc; Walser, Jean‐Claude; Altermatt, Florian
Abstract: Macroinvertebrates serve as key indicators in ecological assessments of aquatic ecosystems, where the composition and richness of their communities are indicative of environmental and anthropogenic change. Established monitoring of macroinvertebrates is expensive and time‐consuming, and relies on expert taxonomic knowledge. In contrast, biomonitoring based on molecular tools can support faster characterization of aquatic communities but needs validation for the target taxonomic groups and the study region. Here, we used data from a biomonitoring program covering a large biogeographic gradient to compare the routine kick‐net method with eDNA metabarcoding. We used two primer pairs targeting COI, one targeting a broad metazoan spectrum (mICOIintF/jgHCO2198) and another more recently developed primer pair optimized for the detection of freshwater invertebrates (fwhF2/EPTDr2n). We used the data of the macroinvertebrate monitoring with a focus on the orders of Ephemeroptera, Plecoptera, and Trichoptera across 92 rivers in Switzerland, covering four continental drainage basins and an elevational range from 198 to 1650 m a.s.l. Across all sample sites, the kick‐net detected more distinct taxa than either of the metabarcoding approaches. At a site level, however, both primer pairs detected on average more species. Comparing both primer pairs, the fwhF2/EPTDr2n primer pair captured more species assigned to the indicator groups Ephemeroptera, Plecoptera, and Trichoptera, and showed a significantly larger overlap with the kick‐net method. However, the community composition still varied significantly among the different metabarcoding approaches. Fewer Trichoptera species were recovered by eDNA, whereas the fwhF2/EPTDr2n primer pair detected more Plecopterans than the other two approaches. This study highlights the importance of the optimization and validation of novel molecular approaches under consideration of the target organismal group and the study area. Abstract : In this study, we analyzed macroinvertebrate communities assessed with both kick‐net sampling and eDNA metabarcoding across a biogeographically diverse region with a particular focus on Ephemeroptera, Trichoptera, and Plecoptera. Specifically, we compared characteristic alpha and beta diversity patterns between the kick‐net and two current CO1 primer pairs at 92 river sites. In general, both eDNA approaches detected more species locally but kick‐net recovered more distinct species overall.